A Digital Teacher’s Guide to Online Learning With Social Media - Siregar, Eveline; Aswan, Dedy; Kustandi, Cecep (Journal of Nonformal Education, 2023)
Covid-19 pandemic around the world has rapidly changed learning patterns. Students are more interested in social media than online learning.  This is reinforced by recent statistics showing increased social media use worldwide during the Covid-19 pandemic. Social media has become an attractive alternative for teachers in online learning activities because ready to use, and many students use it. The use of social media should encourage active, interactive, communicative, creative, and collaborative learning in students because they are used to using it. This research aims to develop a digital guide to help teachers design online learning using social media. This research uses a qualitative approach through the case study to make the model allow the teacher to develop online learning with social media by Combining two models, the ASSURE Model and the Conley and Sabo Model. This research collaborates with high school teachers to conduct focus group discussions. The results of this study illustrate the teacher's view of the digital guidelines developed. Limited ability to use technology is one of the things to consider. This online learning digital guide motivates teachers to continue to innovate amid the covid-19 pandemic. The digital Guidelines guide teachers in online learning to develop online learning in social media, so students feel comfortable studying.